Conflict Management Resolution in Organization - Angger Sulistyarini; Khairun Najwah; Lathifah Fathimah; Nuriana Sari; Shanty Komalasari; Ceria Hermina (International Conference on Psychology and Education (ICPE), 2023)
: Each human life journey cannot be separated from problems. The problems faced are increasingly growing and complex. Few individuals who experience problems will feel pressure within themselves, leading to stress. One of the problems that we often encounter in the reality of life is the existence of conflict in an organization. It cannot be denied that the large number of individuals who gather in a shelter has the potential to cause mild conflicts to even serious ones, which can be caused by two factors, internal and external. Leaders, members, and the surrounding ranks will likely experience a conflict. If conflicts that occur in organizations are not managed properly, these conflicts can disrupt the organization's running. If the conflict cannot be resolved, then the problem will become more serious. Therefore, every organization must be able to manage conflict management. Implementing conflict management is to build and maintain unity within the organization. Improve the ability to resolve conflicts and examine the gaps that exist in the organization.